2008
DOI: 10.1371/journal.pbio.0060292
|View full text |Cite
|
Sign up to set email alerts
|

COPI Complex Is a Regulator of Lipid Homeostasis

Abstract: Lipid droplets are ubiquitous triglyceride and sterol ester storage organelles required for energy storage homeostasis and biosynthesis. Although little is known about lipid droplet formation and regulation, it is clear that members of the PAT (perilipin, adipocyte differentiation related protein, tail interacting protein of 47 kDa) protein family coat the droplet surface and mediate interactions with lipases that remobilize the stored lipids. We identified key Drosophila candidate genes for lipid droplet regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
319
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(332 citation statements)
references
References 78 publications
13
319
0
Order By: Relevance
“…Several studies show that down-regulation of the ARF1-COPI pathway induces LD enlargement (Beller et al 2008;Guo et al 2008;Soni et al 2009). It was conjectured that the ARF1-COPI pathway might increase lipolysis at LDs by modulating PAT protein composition in LDs and/or targeting ATGL to LDs.…”
Section: Lipid Droplets In the Cellular Context Interactions With Othmentioning
confidence: 99%
“…Several studies show that down-regulation of the ARF1-COPI pathway induces LD enlargement (Beller et al 2008;Guo et al 2008;Soni et al 2009). It was conjectured that the ARF1-COPI pathway might increase lipolysis at LDs by modulating PAT protein composition in LDs and/or targeting ATGL to LDs.…”
Section: Lipid Droplets In the Cellular Context Interactions With Othmentioning
confidence: 99%
“…5,6,[14][15][16][17][18]43 Although TPD52 did not emerge as a strong candidate from these collective studies, the direct expression of TPD52 in cultured cells resulted in significantly increased LD numbers. 7 This finding suggests that there may be other important regulators of LDs identified through RNAi screening and proteomics approaches that are yet to be prioritised for further study.…”
Section: Resultsmentioning
confidence: 92%
“…The mouse Tpd52 ortholog was reported to be upregulated 5-fold in obese versus lean mouse adipose tissue, 13 and knock-down of the ancestral C. elegans TPD52 ortholog F13E6.1 was subsequently associated with reduced lipid storage. 14 However, this latter result was not supported by several whole genome RNAi screening studies in D. melanogaster, [15][16][17] although a proteomics study reported a moderate association between the ancestral D. melanogaster TPD52 ortholog CG5174 and LDs. 18 In both these C. elegans and D. melanogaster studies, 14,18 TPD52 orthologues were identified as anonymous proteins, and the The green bar includes a 14-3-3 binding motif, whereas the purple bar represents an alternatively-spliced region termed insert 2 (Ins 2), which is present in some TPD52L2 isoforms, but not other TPD52-like proteins.…”
Section: Early Evidencementioning
confidence: 96%
See 1 more Smart Citation
“…By mediating the delivery of enzymes to this compartment, the COPI system might help control the homeostasis of lipids in the cell (Beller et al 2008;Soni et al 2009), although carriers with cargo indicative of this pathway have not yet been described.…”
Section: Roles Of the Copi Coat Role In The Early Secretory Pathwaymentioning
confidence: 99%